Disseminated Nocardiosis Caused by Nocardia farcinica in Two Puppy Siblings - Flavia Zendri; Peter Richards-Rios; Iuliana Maciuca; Emanuele Ricci; Dorina Timofte (Veterinary Sciences, 2022)
Systemic nocardiosis due to Nocardia farcinica has not been reported in canine outbreaks. Two 14-week-old female Dogue de Bordeaux siblings presented with fever and severe, acute onset limb lameness; traumatic lesions with evidence of infection were identified over the lame limbs of both dogs. The patients were euthanised owing to lack of therapeutic response and rapid escalation to systemic infection with central nervous system manifestations. The post-mortem changes consisted of multiple disseminated abscesses, mainly affecting the skin and subcutis at the limb traumatic injuries, local and hilar lymph nodes, lung, kidney and brain. Bacterial culture and identification via MALDI-TOF and 16S rRNA sequencing revealed Nocardia farcinica from several of these sites in both dogs. Clinical significance of the isolate was supported by cytology of the post-mortem organs’ impression smears showing numerous branching filamentous bacteria associated with inflammation. The organism displayed marked multidrug-resistance. No history of immunosuppression was available, and immunohistochemistry ruled out viral pathogens as canine distemper and parvovirus. N. farcinica should be considered as a potential differential cause of sudden lameness and systemic infection in dogs with traumatic skin lesions over the limbs. This is the first reported small-scale outbreak of systemic nocardiosis in dogs due to N. farcinica.